LEPROSY DETECTION USING IMAGE PROCESSING AND DEEP LEARNING - Suresh Kumar; HARSHIT Jain; SRIVINAYAK CHAITANYA ESHWA (Journal of Global Pharma Technology, 2017)
Leprosy, generally called as Hansen's ailment, is an enervating and ceaseless bacterial malady. As indicated by World Health Organization's report, there were 189,000 uninterrupted occurrences of Leprosy in 2012 with 230,000 new conclusions. Though it is reparable at later stages, an early conclusion expects nerve deliberation and the inadequacies it causes. The makers thusly put forward a Convolutional Neural Network based building for Leprosy damage affirmation. To set up the framework, researchers and scientist use DermnetNz datasets close by web scratched pictures to finish a best accuracy of 91.6% on a dataset split into 60% of get ready pictures, 20% of pictures are used for cross endorsement and 20% for testing of the results.